The Effect of Implementing the Problem Based Learning Model on the Motivation and Learning Outcomes of Class XI TKRO Students in the Light Vehicle Engine Maintenance Subject at SMK Negeri 1 Pangaribuan - Pakpahan, Dandri Natanael; Siregar, Riski Elpari (International Journal of Applied Research and Sustainable Sciences, 2024)
This research aims to determine the effect of applying the problem-based learning (PBL) learning model on student motivation and learning outcomes in light vehicle engine maintenance subjects. This type of research is quasi-experimental, with the research design used being a pretest-posttest control group design. The research results showed that in the experimental class, it was obtained pretest 48.12 and initial motivation 47.63%, posttest experimental class obtained 76.8 and final motivation. 6%, while in the control class obtained pretest 47.15 and initial motivation 45.78%, posttest obtained 70.06 and final motivation 59.6%, so it was concluded that there was a positive influence of the application of the problem-based learning model on student motivation and learning outcomes.